BENTUK DESAIN PRODUK KRIYA DARI LIMBAH KAYU PADA PRODUK CENDERAMATA - Washinton, Rahmad; Ranelis, Ranelis; Malik, Kendall; Yandri, Yandri; Alipuddin, Alipuddin (INSTITUT SENI INDONESIA PADANGPANJANG, 2023)
The research entitled